Boklakh D. Yu. City topos in the poem «In Wilno, the glorious city» by T. G. Shevchenko: synchronization of historical events and tragic circumstances of life in spatial continuum of the city - Boklakh D. Yu. (Philological Treatises, 2020)
The city topos is an important spatial dominant of the city image of Taras Shevchenko’s works. The city topos of the poem «In Wilno, the glorious city» is a spatial constuct in the time of the city attributes, along with feelings and impressions of the narrator about the events occurring in the specified locuses. The topos of Wilno city includes space coordinates of synchronization of the historic flowing course of existence with the life drama of love of a young man to a girl of another faith. The poetic topos of the city is not described in detail, only certain space forming elements are presented: the University, the city gate, boulevard, house, window, Wilia river, Zakret area, which become the locuses and the expressers of the described events. However, these elements are sufficient to outline the city poetic topos of Wilno and characterize the life drama of the characters. The poetic topos of the city simultaneously becomes a historical background displaying the time of closing down Wilno University by the Russian czarist regime in 1832, depicts the existential collision of the unhappy characters’ love.